Menyoal Keabsahan Hadis-Hadis Keintiman; Studi Analisis Kitab Qurratul Uyun Karya Syaikh Muhammad Al-Tahami bin Madani - Khairul Muttaqin (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2020)
Qurratul Uyun is a book in which many explain about marriage. The book created by Syaih Muhammad al-Tahami bin Madani. The book is widely found and taught in the huts of salaf boarding schools in order to provide knowledge that is populated for student who want to get married. One discussion in the Qurratul Uyun is about intimate relationships include the right day and the inappropriate for intercourse, intercourse and intercourse reward. The discussions are explained by quoting the Prophet's hadiths to corroborate the discussion. However, the hadith which is used as the foundation is not all shahih but there are some hadits whose quality is dha’if even maudhu’. The method used in this paper is the method of library research where more refers to the sources of books in the form of books of hadith and books biography of the hadith narration in researching the quality of the hadith. After a thorough study, it was found that not all of the hadiths of intimacy mentioned in the Qurratul Uyun are worth dha’if. There are some who are shahih and can be used as a legal basis. But there are also some hadith intimacy in the book that is worth dha’if so it can’t be used as a legal basis. Some of the hadiths are also worth dha’if but supported with other hadiths of better quality so that can still be the basis of law and its content can be practiced.